Profile sprawiedliwości we współczesnej prasie opinii = The profiles of justice in contemporary Polish weeklies - Polkowska, Laura (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The scetch is dedicated to the concept of justice in contemporary Polish weeklies. In the article, I use the profiling method developed by Jerzy Bartmiński and his team from Lublin. In the analysis, I take into account the differences between how liberal (?Newsweek? and ?Polityka?) and conservative (?Do Rzeczy? and ?W Sieci?) weeklies present justice.
Keywords: sprawiedliwość; wartość; profilowanie; tygodniki opinii; semantyka; justice; values; linguistic profiling; weeklies; semantic